The Survival Out Of Water And Evaporative Water Loss In Anguilla bengalensis Related To Relative Humidity - Mallikaraj, D (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Oxygen availability in aquatic habitats is a major ecological factor influencing the distribution of fish. The fish has limited potentialities to survive out of water. Higher humidity enhances the survival rate and minimizes evaporative water loss. Humidity plays an important role in the survival capacity of fish. At 35 % - 40 % relative humidity an A. bengalensis survive at 3 h - 5 h.